Periodontal Diseases and Associated Factors among Type 1 Diabetes Mellitus Patients from Selected Clinics in Dhaka, Bangladesh - Sultana, Nahid; Jacob, Pulikkotil Shaju (Anwer Khan Modern Medical College Journal, 2021)
Introduction: Periodontal disease and diabetes mellitus are the two most prevalent chronic diseases and global burdens in the world. Periodontal disease comprises gingivitis and periodontitis. An increasing trend of periodontal disease is reported among diabetic patients in Bangladesh. Limited studies have investigated the association between type 1 diabetes mellitus and periodontal disease in Bangladesh. This study, therefore, aims to investigate the association of demographic characteristics, lifestyle factors, diabetic-related factors, and oral hygiene practice with periodontal disease among type 1 diabetes mellitus in Dhaka, Bangladesh. Methods: Survey and clinical examination of this cross-sectional study were conducted in three well-known clinics in Dhaka. A total of 182 participants were clinically examined based on inclusion and exclusion criteria. Results: A higher prevalence of periodontitis was found compared to gingivitis among type 1 diabetes mellitus. About 30.2% of the respondents had moderate periodontitis, followed by mild periodontitis 28.6%. The majority of respondents (30.8%) had mild gingivitis and only 14.8% had moderate gingivitis. Furthermore, proportions of periodontitis and gingivitis were positively associated with age [(aOR1.12 (95%cis=1.07, 1.17)] and lower education. A significant association of periodontitis was found with the duration of diabetes [(aOR) 0.95 (95%cis=0.90, 0.99)] and frequency of toothbrushes (42-fold greater). Conclusions: The findings of this study imply that dentists should emphasize on patients for well metabolic control to prevent the progression of periodontal disease. AKMMC J 2022; 13(1) : 22-31